Overview Implementation of Precast U-Ditch Drainage Construction on Jalan Otto Iskandardinata - Tama, Brian Ricki; Yatnikasari, Santi; Handayani, Elvira; Umi, Zulfikar; Agustina, Fitriyati (LPPI Universitas Muhammadiyah Kalimantan Timur (UMKT), 2024)
The increasing use of transportation infrastructure in Indonesia demands the development of facilities and infrastructure to enhance the quality of public services. Kalimantan Timur is a rapidly growing province. The rising population of Kalimantan Timur necessitates the construction of supportive facilities and infrastructure. Drainage refers to the action or process of draining/disposing of water, resulting from human activities like household wastewater, industrial wastewater, as well as natural processes such as rain, water accumulation, floods, and groundwater level reduction. The Drainage Project aims to improve the drainage system to reduce flood and waterlogging risks while preserving water quality, accommodating the growth of the population and the need for supporting infrastructure like housing, schools, and healthcare facilities. In the Drainage Development Project on Jalan Otto Iskandardinata, the precast concrete method with dimensions of 100x70x20 is used. The implementation of the U-Ditch Precast Drainage Project on Jalan Otto Iskandardinata is expected to alleviate flood issues. Before commencing the work, various tests such as the Slump Test, Compressive Strength Test, Hammer Test, and Tensile Strength Test are conducted to ensure compliance with the required specifications. Occupational Health and Safety (OHS) measures have been applied to the Drainage Project. Each stage of the project's implementation must be supervised by field inspectors to ensure the project runs smoothly and meets the required quality standards.